上下顎歯肉に発生したメトトレキサート関連リンパ球増殖性疾患の1例 - 鈴木, 泰明; 浅井, 知子; 古森, 孝英; 竹内, 純一郎; 木本, 明; 古土井, 春吾 (日本口腔外科学会雑誌, 2013)
Patients with rheumatoid arthritis often receive methotrexate (MTX). Recently, it has been shown that MTX can cause B cell lymphoma, non-Hodgkin's lymphoma. B cell lymphoma caused by MTX is referred to as a methotrexate-associated lymphoproliferative disorder (MTX-LPD) and is recognized by the World Health Organization and included among immunodeficiency-associated LPD. We describe a rare case of MTX-LPD with osteonecrosis of the jaw of maxilla and mandible in which spontaneous complete remission was achieved.